Comparative Proteome and Phosphoproteome Analyses Reveal Different Molecular Mechanism Between Stone Planting Under the Forest and Greenhouse Planting of Dendrobium huoshanense - Wu, Liping; Meng, Xiaoxi; Huang, Huizhen; Liu, Yingying; Jiang, Weimin; Su, Xinglong; Wang, Zhaojian; Meng, Fei; Wang, Longhai; Peng, Daiyin; Xing, Shihai (Frontiers in Plant Science, 2022)
The highly esteemed Chinese herb, Dendrobium huoshanense, whose major metabolites are polysaccharides and alkaloids, is on the verge of extinction. The stone planting under the forest (SPUF) and greenhouse planting (GP) of D. huoshanense are two different cultivation methods of pharmaceutical Dendrobium with significantly different morphology, metabolites content and composition, and medication efficacy. Here, we conducted proteomics and phosphoproteomics analyses to reveal differences in molecular mechanisms between SPUF and GP. We identified 237 differentially expressed proteins (DEPs) between the two proteomes, and 291 modification sites belonging to 215 phosphoproteins with a phosphorylation level significantly changed (PLSC) were observed. GO, KEGG pathway, protein domain, and cluster analyses revealed that these DEPs were mainly localized in the chloroplast; involved in processes such as posttranslational modification, carbohydrate transport and metabolism, and secondary metabolite biosynthesis; and enriched in pathways mainly including linoleic acid metabolism, plant-pathogen interactions, and phenylpropanoid, cutin, suberin, and wax biosynthesis. PLSC phosphoproteins were mainly located in the chloroplast, and highly enriched in responses to different stresses and signal transduction mechanisms through protein kinase and phosphotransferase activities. Significant differences between SPUF and GP were observed by mapping the DEPs and phosphorylated proteins to photosynthesis and polysaccharide and alkaloid biosynthesis pathways. Phosphorylation characteristics and kinase categories in D. huoshanense were also clarified in this study. We analyzed different molecular mechanisms between SPUF and GP at proteomic and phosphoproteomic levels, providing valuable information for the utilization of this medicinal plant.